Absences and opacities: Reading "hidden" stories of seafaring in B. Traven's Ship of the Dead and Francisco Goldman's The Ordinary Seaman. Issue 1 (2nd January 2018) - Gräbner, Cornelia
ABSTRACT: This article engages the historical approach to the "Hidden Atlantic" (Michael Zeuske) in a complementary, literature-based analysis. It argues that the diverse facets of the "hidden" require diverse methodological approaches; firstly, because the "hidden" has several dimensions, and secondly, because the ethical impetus of the cultural analyst or the historian requires a choosing of sides. Authors of works labelled as "literary" or "fiction, " which are nevertheless known to have a close relationship to real-life experience, negotiate this fine line. The article analyses in greater detail two such works – B. Traven's Das Totenschiff (1926) and Francisco Goldman's The Ordinary Seaman (1997) – with reference to their treatment of the " Totenschiff " and its crews in the context of predatory capitalism. In the first instance, the article explores two dimensions of the "hidden": the "forcibly rendered absent" (Boaventura de Sousa Santos) and the "opaque" (Édouard Glissant). The literary figure of the "Totenschiff, " the "ship of the dead, " is deployed by the authors to bring to the attention of the readers the plight of the crewmembers who have been expulsed (Saskia Sassen) from society, the callousness and impunity of the perpetuators and agents of predatory capitalism who exploit them, and the complicity of the "civilized" populations who acquiesce to this expulsion. While they do this, the authors use "literariness" to preserve the opacity that protects the expulsed. Through a comparative analysis of the interplay of absences and opacities in both novels, with a particular focus on deviant and hegemonic masculinities, this article explores possibilities for cultural analysts to engage with the "hidden, " without jeopardizing the relative safety granted to the expulsed by opacity.